2020
DOI: 10.1038/s41597-020-0402-1
|View full text |Cite
|
Sign up to set email alerts
|

Gaze, behavioral, and clinical data for phantom limbs after hand amputation from 15 amputees and 29 controls

Abstract: Despite recent advances in prosthetics, many upper limb amputees still use prostheses with some reluctance. They often do not feel able to incorporate the artificial hand into their bodily self. Furthermore, prosthesis fitting is not usually tailored to accommodate the characteristics of an individual's phantom limb sensations. these are experienced by almost all persons with an acquired amputation and comprise the motor and postural properties of the lost limb. this article presents and validates a multimodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In literature, most studies reported that a majority of amputees continue to dream about themselves with an intact body [ 36 , 45 , 46 , 47 , 48 ] even if, in some cases, there is a difference between how the phantom limb is perceived in the waking state and in dreams [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, most studies reported that a majority of amputees continue to dream about themselves with an intact body [ 36 , 45 , 46 , 47 , 48 ] even if, in some cases, there is a difference between how the phantom limb is perceived in the waking state and in dreams [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In amputees, phantom limb sensations and telescoping are widely present with most individuals experiencing some type of phantom phenomena at some point, post-amputation [ 26 , 27 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eye tracking reflects the user's visual attention and gaze direction [20], recorded from cameras or glasses that capture the movement of the eyes and pupils and processed by using methods such as gaze fixation, gaze switching, or gaze estimation to decode the user's intention [12,21]. Gaze fixation is used when the user is looking at a specific target for a certain amount of time and activating a corresponding hand gesture [22,23].…”
Section: Prosthetic Hands Controlmentioning
confidence: 99%
“…The model’s limbs were pictured in the first-person (1pp, n = 128) or third-person (3pp, n = 128) perspective, and belonged to the object solidity constraint (n = 128) or limb solidity constraint (n = 128) condition. These two conditions were included on the basis of two strains of evidence: i) whether individuals with amputations show obstacle shunning or not depends on whether the phenomenal space occupied by the phantom limb overlaps with that of biological (i.e., the contraleral limb) or non biological (a wall) matter (Saetta et al, 2020a), and ii) obstacle shunning experience is related to LAMP (Saetta et al,. 2018).…”
Section: Studymentioning
confidence: 99%
“…Experienced by almost all individuals with an amputation (Ramachandran & Hirstein, 1998), phantom limb awareness refers to the persistence of the motor and postural representations of a limb despite its physical absence (Brugger, 2006). The phantom limb might be intentially moved to various degrees or completely immobilized (Saetta et al, 2020a). Training to execute impossible movements with a phantom limb has shown to enhance the visually guided perception of physically impossible movements, regardless of the SOAs (Moseley & Brugger, 2009).…”
Section: Introductionmentioning
confidence: 99%